U.S. Family Forest Owners' Forest Management for Climate Adaptation: Perspectives From Extension and Outreach Specialists - vonHedemann, Nicolena; Schultz, Courtney A. (Frontiers in Climate, 2021)
In the United States (US), family forest owners, a group that includes individuals, families, trusts, and estates, are the largest single landowner category, owning approximately one-third of the nation’s forests. These landowners’ individualized decision-making on forest management has a profound impact on US forest cover and function at both local and regional scales. We sought to understand perceptions among family forest specialists of: climate impacts and adaptation options across different forested US regions; how family forest owners are taking climate adaptation into consideration in their forest management, if at all; and major barriers to more active management for adaptation among family forest owners. We conducted semi-structured interviews with 48 forest experts across the US who work with family forest owners, including extension specialists, state forestry agency employees, and consulting foresters who focus on family forest engagement. Our interviewees shared details on how both climate change impacts and forest management for climate adaptation vary across the US, and they perceived lack of active forest management by family forest owners. They explained that western forest landowners confronting the imminent threat of catastrophic wildfires are more likely to see a need for active forest management. By contrast, in the east, where most forestland is privately owned, interviewees said that landowners see relatively fewer climate impacts on their forests and less need for forest management to respond to climate change. Perceived barriers to more active family forest management for climate adaptation include the lack of more robust markets for a wide range of forest products, a higher capacity forestry workforce, education and assistance in planning forest management, and addressing the issue of increased parcelization of family forest lands. We situate these perceptions in conversations on the role of boundary organizations in climate adaptation, how individual adaptation occurs, and how governing methods frame adaptation possibilities.